INTERNATIONAL TREATIES – THE CHALLENGES OF THE MULTILATERAL TREATY SYSTEMS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article analyzes the challenges of multilateral international treaty-making. It focuses on key issues such as implementation, state consent, conflicting interests, and ratification processes. The author emphasizes that effective treaty-making requires harmonization of domestic norms, sufficient resources, political will, and coordination among states. The study highlights the difficulties in achieving agreements that serve both national and international interests and stresses the need for collaboration and shared commitment among the international community to ensure successful treaties.